(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Enhancements are required in promoting scientific honesty and decent practices in scholarly work, specifically in acknowledging the contributions of the authors. It is a sporadic situation to involve in plagiarism unintentionally when any academic work is used. Hence, it is quite crucial to know the attitudes of students towards plagiarism. Therefore, the current research is aimed at identifying the attitude of students who study at Uzbekistan State world languages university. The research is based on the questionnaire and the results are calculated through the quantitative method which are given in the form of diagrams and charts.